Implementation of Cloud Computing on Website- Based Car Rental System at Dampit Trans Solo - Tegar Danardana Lokananta (Universitas Mercu Buana Yogyakarta, 2025)
A website application must have a scalable, flexible, and reliable server infrastructure to facilitate the development of a system from design to distribution to users. With its various outstanding services, such as Google App Engine (GAE), Google Cloud SQL, and Google Cloud Storage, Google Cloud has become one of the cloud computing service providers that successfully provides solutions to these infrastructure needs. The case study presented in this research is the development of a website-based car rental information and management system at Dampit Trans Solo company, utilizing cloud computing infrastructure. This system is developed to provide solutions for Dampit Trans company and customers by simplifying the company's business processes and providing a cost-effective website infrastructure. System quality testing is conducted using three methods: black box testing, System Usability Scale (SUS), and access speed evaluation. The black box testing showed that the system is functional and error-free. The SUS testing resulted in an average score of 80.04, interpreting the system as usable in real-world scenarios with a